2019
DOI: 10.3390/ijms20194793
|View full text |Cite
|
Sign up to set email alerts
|

Mildew Resistance Locus O Genes CsMLO1 and CsMLO2 Are Negative Modulators of the Cucumis sativus Defense Response to Corynespora cassiicola

Abstract: Corynespora leaf spot caused by Corynespora cassiicola is one of the major diseases in cucumber (Cucumis sativus L.). However, the resistance mechanisms and signals of cucumber to C. cassiicola are unclear. Here, we report that the mildew resistance locus O (MLO) genes, CsMLO1 and CsMLO2, are both negative modulators of the cucumber defense response to C. cassiicola. Subcellular localization analysis showed that CsMLO1 and CsMLO2 are localized in the plasma membrane. Expression analysis indicated that the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…CsMLO1 and CsMLO2 were isolated previously and functionally characterized in C. cassiicola -infected cucumber leaves [15]. The sequences of calmodulin-7 (A0A0A0KWT3) were aligned with the cucumber genome database using the service provided by .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…CsMLO1 and CsMLO2 were isolated previously and functionally characterized in C. cassiicola -infected cucumber leaves [15]. The sequences of calmodulin-7 (A0A0A0KWT3) were aligned with the cucumber genome database using the service provided by .…”
Section: Resultsmentioning
confidence: 99%
“…Wang has shown that secondary metabolism and ROS accumulation play important roles in disease resistance during cucumber– C. cassiicola interactions [16]. Moreover, we first found that CsMLO1 is a negative modulator that regulates the defense response of cucumbers to C. cassiicola [15]. Next, the relationships of CsPR and ROS -associated genes with the overexpression and silencing of CsMLO1 in noninfiltrated cucumber plants was investigated, and the results show that CsMLO1 acts as a negative regulator to activate/inhibit the expression of related genes [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations